β-Glucosidase Activity by Sequential Injection Analysis: Evaluation of the Free and Immobilized Enzyme - V Vidal, Cedillo-Perez; V Aurora, Quintero-Lopez; Ulises Ruben, Carrillo-Medrano; Maria Pilar, Canizares-Macias (Current Analytical Chemistry, 2017)
Background: The implementation of the automation of enzyme based on the evaluation of enzyme activity or the determination of specific analytes has been allowed by the Sequential Injection Analysis (SIA) systems. Objective: Kinetic constants Km, Kcat and Kcat/Km. were evaluated in order to get the behavior of free (homogeneous media) and immobilized on controlled pore glass (heterogeneous media) using a SIA method. Method: Hydrodynamic and chemistry parameters were evaluated using a factorial design 25-1. The kinetics parameters were calculated at 40 °C and 60 °C and at pH 4 and 5. The results were compared with those obtained by a batch method. Results: By SIA, the optimum values for the enzyme free were at pH 4 and 40 °C (Km=1.33±0.05 mM; Kcat=6.80±0.08 s-1 and Kcat/Km=5117.43±132.03 M-1 s-1) and for the immobilized enzyme were at pH 5 and 60 °C (Km=4.85±0.80 mM; Kcat = 0.15±0.008; Kcat/Km =30.92±3.42) although at pH 5 and 40 °C Kcat was higher (0.56±0.024) indicating better exchange of substrate molecules at active site. 40 °C and pH 4 (0.23±2.2x10-4 mM) were the optimum conditions to get the higher efficiency by the batch method. Conclusion: The results show that by SIA it is possible to determine the catalytic and kinetic efficiencies guaranteed with an effective control of the reaction conditions as consequence of the well defined transport. The results also show that the affinity from the enzyme to the substrate as well as the kinetic reaction change when the enzyme is immobilized because, probably, the structure of the active sites is different.
Keywords: sequential injection analysis